Theory of decision-making for treatment of chronic constipation - Abdul Wahab, Patimah; Mohd Yusoff, Dariah; Ali, Siti Hawa; Abdul Kadir, Azidah; Lee, Yeong Yeh; Kueh, Yee Cheng (2019)
Throughout theory of decision-making for treatment of chronic constipation, individuals acquire greater insight about the process of elderly making decision for treatment in management of chronic constipation. It has cultural sensitivity and has reference to issues of elderly. The theory suggests relationship of domains that involve in explaining decision-making for treatment of chronic constipation by the elderly